HUBUNGAN ASUPAN MAGNESIUM, SENG, DAN MANGAN DENGAN DIABETES MELITUS GESTASIONAL PADA IBU HAMIL DI WILAYAH KABUPATEN BANTUL - Adelia Suryani Nasution; Effatul Afifah; Emy Huriyati; Bunga Astria Paramashanti; Tri Siswati (Media Gizi Mikro Indonesia, 2023)
ABSTRACT Background: Gestational diabetes mellitus or diabetes experienced during pregnancy occurs due to a metabolic disorder of blood glucose during pregnancy. The prevalence of gestational diabetes mellitus in Indonesia is 1.9% - 3.6%. Intake of mineral nutrients seen from its most important function is to metabolize carbohydrates, proteins, and fats into energy such as magnesium, zinc, and manganese minerals so there is a special attention between macro and micro mineral intake with the incidence of gestational diabetes mellitus. Objective: To examine the correlation between the intake of magnesium, zinc, and manganese of gestational diabetes mellitus in pregnant women in the Public Health Area of Sewon, Banguntapan, and Jetis Bantul District Yogyakarta Special Region. Methods: This research was an observational analytic research with a cross-sectional research design. The sampling technique used purposive sampling method, research subjects are pregnant women who have been done checking urine reduction in trimester I in Bantul Regency working area as many as 136 pregnant women. The data collected include respondent characteristics, fasting blood glucose measurement, and SQFFQ form. The data will be analyzed using Fisher exact with significance level ? <0.05 and mean different test (T-test). Results: Of the 136 respondents, 3 of them (2.2%) included the gestational diabetes mellitus group. Fisher exact test results showed the correlation of magnesium intake with the incidence of gestational diabetes mellitus had p-value = 0.097, the correlation of zinc intake with the incidence of gestational diabetes mellitus had p-value = 0.198 (OR=0,193, 95% CI;0,017-2,189), and the correlation of manganese intake with the incidence of gestational diabetes mellitus has p-value = 0.207 (OR=0,200, 95% CI;0,018-2,271). Conclusion: There was no significant correlation between the intake of magnesium, zinc, and manganese and gestational diabetes mellitus in Bantul District Yogyakarta Special Region (DIY). ABSTRAK Diabetes melitus gestasional atau diabetes yang dialami saat masa kehamilan terjadi akibat adanya gangguan metabolik glukosa darah saat masa kehamilan. Prevalensi diabetes melitus gestasional di Indonesia sebesar 1.9% - 3.6%. Asupan zat gizi mineral dilihat dari fungsinya yang paling penting ialah memetabolisme karbohirdrat, protein, maupun lemak menjadi energi seperti mineral magnesium, seng, dan mangan sehingga perlu adanya perhatian khusus antara asupan makro dan mikro mineral dengan kejadian diabetes melitus gestasional. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan asupan magnesium, seng, dan mangan dengan diabetes melitus gestasional pada ibu hamil di wilayah Puskesmas Kecamatan Sewon, Banguntapan, dan Jetis Kabupaten Bantul. Penelitian ini merupakan penelitian analitik observasional dengan rancangan penelitian cross sectional. Teknik pengambilan sampel menggunakan metode purposive sampling, subyek penelitian adalah ibu hamil yang sudah dilakukan pengecekan reduksi urin di trimester I yang ada di wilayah kerja puskesmas Kabupaten Bantul sebanyak 136 ibu hamil. Data yang dikumpulkan meliputi karakteristik responden, hasil pengukuran kadar glukosa darah puasa, serta pengisian kuesioner SQ-FFQ. Data akan dianalisis menggunakan uji fisher exact dengan tingkat kemaknaan ? < 0.05 dan uji beda rata-rata (T-test). Dari 136 responden, 3 orang diantaranya (2,2%) termasuk kelompok diabetes melitus gestasional. Hasil uji Fisher exact menunjukkan hubungan asupan magnesium dengan kejadian diabetes melitus gestasional memiliki nilai p-value = 0,097, hubungan asupan seng dengan kejadian diabetes melitus gestasional memiliki nilai p-value = 0,198 (OR=0,193, 95% CI;0,017-2,189), dan hubungan asupan mangan dengan kejadian diabetes melitus gestasional memiliki nilai p-value = 0,207 (OR=0,200, 95% CI;0,018-2,271).